Pengembangan Bahan Ajar Refraksionis Optisien Model Dick & Carey di Akademi Refraksi Optisi Leprindo - Muhammad Abdul Ghoni Rohimin; Iskandar Wiryokusumo; Ibut Priono Leksono (Universitas Indraprasta PGRI Jakarta, 2023)
The development of teaching materials for professional ethics of optical refractionists/optometrists for fifth semester students at the LEPRINDO Optician Refraction Academy is expected to produce efficient and effective teaching materials for students and lecturers, thus it makes easier for lecturer in carrying out the lecture process. The development practices programmed model, which is arranged in a systematic order based on a theoretical foundation, by describing the problems that arise in learning, namely Dick and Carey Model. The products can be used as learning resources, as evidenced by expert validation and feasibility tests results. Some students show that the teaching materials for the Refractionist Optimist professional ethics are very feasible with a percentage of 75% and are in accordance with the existing theory.